Elasto-optic properties and internal stress analysis for monoclinic and trigonal crystals. (5th August 2021) - Rinaldi, D.; Montalto, L.; Natali, P.P.; Davì, F.
Abstract: We study the elasto-optic behaviour of monoclinic and trigonal crystals. The eigenvalues and eigenvectors of the dielectric impermeability tensor under stress are evaluated by the means of the approximated formulae obtained by Sirotin. The parameters which characterize Bertin's surfaces and fringe patterns in conoscopic observation are determined as functions of either residual or applied stress. Later, the photoelastic constants, and the rotation of the optic plane and optic axes bisector are estimated in order to allow for the evaluation of the residual or applied stress by conoscopic measurements. Finally, we obtain the dependence of the refraction indices on the stress. The knowledge of these crystal properties is mandatory for applications in high physics energy, security, geological prospection and in crystals for photonics and medical applications. The evaluated photoelastic constants allow the development of methodologies for an easy and fast quality control via stress distribution detections by means of conoscopic observation, even for strongly anisotropic crystals. As a case study we apply these results to the cases of monoclinic Lu2(1-x) Y2x SiO5 (LYSO) and trigonal LiNbO3 (Lithium Niobate).